152k views
2 votes
Ind f(x+h) when f(x) = 3x- 4x^2

1 Answer

3 votes

Answer:

f(x + h) = -4x² - 4h² - 8hx + 3x + 3h

General Formulas and Concepts:

Algebra I

  • Function Notation
  • Expand by FOIL (First Outside Inside Last)
  • Combining Like Terms

Explanation:

Step 1: Define

f(x) = 3x - 4x²

f(x + h) is x = x + h

Step 2: Evaluate

  1. Substitute: f(x + h) = 3(x + h) - 4(x + h)²
  2. Expand [FOIL]: f(x + h) = 3(x + h) - 4(x² + 2hx + h²)
  3. Distribute: f(x + h) = 3x + 3h - 4x² - 8hx - 4h²
  4. Rewrite: f(x + h) = -4x² - 4h² - 8hx + 3x + 3h
User Sanjay Joshi
by
5.3k points